Atmospheric monitoring strategy for the Ali site, Tibet. (March 2015) - Yao, Y; Zhou, Y; Liu, L; Wang, H; Yin, J; You, X; Fu, X
Abstract: The astronomical site survey in China has been carried out since 2003. Remote studies and local surveys are performed over the high plateaus, and candidate sites have been selected and performed site testing measurements. The monitoring results show that Ali area in western Tibet can be the best choice for astronomical observations over East Asian regions. Ali site, near the central town of Ali area, has been further identified for small telescope projects and simultaneously for detailed site characterization, and begun construction in 2010. This paper presents the site monitoring strategy and site development plan of the new Ali observatory.